Mixture of Two Inverse Exponential Distributions Based on Fuzzy Data - Al-Sultany, Shurooq A K; Mohammed, Sahar Ahmed (Al-Nahrain Journal of Science, 2019)
In this paper we will discuss the mixture distribution consisting of two Inverse Exponential Distributions (MTIED) based on fuzzy data. We will study the Maximum Likelihood Estimator (MLE) via the Newton Raphson (NR) algorithm and Bayes estimation under square error loss and quadratic loss functions for the unknown parameters of the distribution, and reliability function. The obtained estimates of the unknown parameters and reliability function are compared numerically through Monte-Carlo simulation study in term of the mean square error (MSE) values and (IMSE) respectively.